INSUFFICIENT PREPARATION OF TEACHING READING: WHAT SHOULD TEACHER CHALLENGE? - Imroatus Solikhah (Center of Language and Cultural Studies [CLCS], 2018)
This paper for all intents and purposes is to describe issues and challenges of teaching reading in the EFL classroom. Basically, this paper claims that teaching reading and reading competences are failed to achieve and students get insufficient knowledge and skills through reading. Teaching reading has been colored with problems that make students boring. The problems include: Literacy in general word list vocabulary: Difficult vocabulary terms, Academic vocabulary, Complexity of grammar, Inappropriate texts, Complexity of academic text, Reading habits and culture, Lack of schema activation, Lack of motivation to read, Insufficient preparation in teaching reading. This paper proposes alternative to teaching reading in context of academic purposes in the university level.